Glavni izzivi občinskega prostorskega načrtovanja - Pličanič, Senko (Podjetje in delo, 2025)
Municipal spatial (land-use) planning is extremely important for Slovenia’s economic development and for the protection of our environment. Unfortunately, in practice it often represents an obstacle to economic development and likewise fails to ensure effective environmental protection. In this paper, I have presented the key shortcomings of municipal spatial planning as well as guidelines for addressing these deficiencies.
Keywords: Lokalna samouprava; Regionalno planiranje